VD_FINDINFO Jug / 2025 / 84 vom 12. August 2024 - VD Tribunal cantonal (2024)
EXPULSIONDROIT PÉNAL, APPRÉCIATION DES PREUVES, AFFILIATION À UNE BANDE | 66a al. 1 let. c CP, 66a al. 1 let. d CP, 66a al. 2 CP